Desarrollo de híbridos de Brachiaria resistentes a cuatro especies de salivazo (Homoptera: Cercopidae) - Sotelo, G.; Cardona Mejía, César; Miles, John W. (2003)
The production and identification of Brachiaria hybrids with high levels of resistance to Aeneolamia varia (F) and the characterization of mechanisms of resistance to other spittlebug species are very important steps in a Brachiaria breeding scheme. This scheme is based on the following.biannual cycle of recurrent selection: a) Production and field testing of thousand of hybrids; b) Selection for agronomic adaptation and performance; c) Greenhouse evaluation for resistance to A. varia (500-1000 hybrids with two repetitions per hybrid); d) Detailed evaluation for resistance to A. varia and other spittlebug species (ca. 100 hybrids, ten repetitions per hybrid); e) Field testing for resistance and agronomic performance of those hybrids selected for resistance under greenhouse conditions. Comparison of average damage scores in two consecutive cycles of selection showed that damage levels decreased from 3,2 to 2,3 (P < 0.05) in a scale of 1 to 5, i. E., about 28% gain in resistance. These data confirm the reliability of both the selection scheme and the evaluation methodology. Significant advances were made in the understanding of differential mechanisms of resistance of Brachiaria sp. to four species of spittlebug and in the identification of hybrids with multiple resistance to two or more spittlebug species.